Characterization and evolution of hedenbergite-hastingsite-biotite-garnet orthogneiss in the region of the alterosa paleo-suture zone, southern portion of southern brasÍlia orogen - Leme, Thaís Güitzlaf [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP]; Zanardo, Antenor [UNESP]; Lima, Filipe Goulart; Montibeller, Cibele Carolina [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
In the southwest of Minas Gerais state, Santa Cruz do Prata district region, inserted in a context of high-pressure rocks attributed to the Araxá Group, in the southern portion of the Southern Brasília Orogen, an occurrence of hedenbergite-hastingsite-biotite-garnet orthogneiss body was recorded, whose mineral association is uncommon. This paper presents petrography, mineral chemistry, geochemistry, geothermobarometry, and model age data of the occurrence. The orthogneiss configures a lenticular body, oriented according to the E-W direction, parallel to the direction of the regional shear zones. It has isotropic to anisotropic structure and it can show much more foliated and oriented domains, as result of the greater degree of deformation. The mineral association present in the less deformed portions (andesine + orthoclase + quartz + garnet + hedenbergite), the textural and petrological features in line with the chemical and isotopic data, suggest a paleoproterozoic igneous protolith, metamorphosed into granulite facies (high pressure). The calculated pressure and temperature conditions (around 11.0-10.5 kbar and 750-700ºC) correspond to the regional metamorphic re-equilibration. Geochemical data indicate characteristics similar to rocks generated in magmatic arcs.
Caracterização e evolução de hedenberguita-hastingsita-biotita-granada ortognaisse na região da zona de paleo-sutura de alterosa, porção sul do orógeno brasília meridional
Keywords: Araxá Group; Brasília Belt; Campo do Meio Shear Belt; Granulite facies